1958
DOI: 10.1073/pnas.44.12.1237
|View full text |Cite
|
Sign up to set email alerts
|

Complementation at the Ad-4 Locus in Neurospora Crassa

Abstract: Three cases of complementation between allelic mutants in heterocaryons of Neurospora crassa have been reported in which the individual homocaryons lack a specific enzymatic activity.'-3 More recent and apparently similar phenomena have been observed in which data relating to the involvement of a single enzyme are still lacking.4 6The present paper presents a detailed analysis of heterocaryon complementation between ad-4 mutants, each of which has impaired adenylosuccinase activity. The results suggest that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1959
1959
2002
2002

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 7 publications
1
20
0
Order By: Relevance
“…In E. coli there appears to be no additional pathway to ornithine. 4 The study has been extended to include not only arginine-repressible strains but also strains in which arginine does not have this effect.…”
mentioning
confidence: 99%
“…In E. coli there appears to be no additional pathway to ornithine. 4 The study has been extended to include not only arginine-repressible strains but also strains in which arginine does not have this effect.…”
mentioning
confidence: 99%
“…The majority of the alleles are group A members, which show no complementation with any other alleles. Woodward, Partridge and Giles (1958) found that the greater the distance between two ranges of action, as represented on the cornplementation map, the more vigorous was the heterocaryotic growth.…”
Section: Results (I) Heterocaryon Corn Piementationmentioning
confidence: 99%
“…Almost all amylase mutant genes belong to one locus with the exception of one gene (ae5) according to the results from the present genetic studies. In this point further details of the characterization of these amylase genes have been investigated with the heterocaryon-test for complementation (Giles et al 1957;Woodward et al 1958 <Lacy and Bonner 1961), resulting in restoration of growth on starch.…”
Section: Discussionmentioning
confidence: 99%